Cold War binaries and the culture of consumption in the late Soviet home. (15th February 2016) - Reid, Susan E.
Abstract : Purpose: – The purpose of this paper is to challenge Cold War binaries, seeking a more nuanced understanding of popular experience of change in the Soviet Union's last decades. This was a period of intensive modernization and rapid transformation in Soviet citizens' everyday material environment, marked by the mass move to newly constructed housing and by changing relations with goods. Design/methodology/approach: – To probe popular experience and changing meanings, the paper turns to qualitative, subjective sources, drawing on oral history interviews ( Everyday Aesthetics in the Modern Soviet Flat, 2004-2007). Findings: – The paper finds that qualitative changes took place in Soviet popular consumer culture during the 1960s-1970s, as millions of people made home in new housing amid the widespread media circulation of authoritative images representing a desirable modern lifestyle and modernist aesthetic. Soviet people began to make aesthetic or semiotic distinctions between functionally identical goods and were concerned to find the right furniture to fit a desired lifestyle, aesthetic ideal and sense of self. Research limitations/implications: – The problem is how to conceptualize the trajectory of change in ways that do justice to historical subjects' experience and narratives, while avoiding uncritically reproducing Cold War binaries or perpetuating the normative status claimed by the postwar West in defining modernity and consumer culture. Originality/value: – The paper challenges dominant Cold War narratives, according to which Soviet popular relations with goods were encompassed by shortage and necessity. It advances understanding of the specific form of modern consumer culture, which, it argues, took shape in the USSR after Stalin.